Low-level mosaic trisomy 21 at amniocentesis and cordocentesis in the second trimester in a pregnancy associated with positive non-invasive prenatal testing for trisomy 21, perinatal progressive decrease of the trisomy 21 cell line and a favorable fetal outcome - Chih-Ping Chen; Fang-Tzu Wu; Yen-Ting Pan; Peih-Shan Wu; Meng-Shan Lee; Chien-Ling Chiu; Wayseen Wang (Elsevier, 2024)
Objective: We present low-level mosaic trisomy 21 at amniocentesis and cordocentesis in a pregnancy associated with a favorable fetal outcome. Case Report: A 26-year-old, primigravid woman underwent amniocentesis at 17 weeks of gestation because of positive non-invasive prenatal testing (NIPT) for trisomy 21 at 16 weeks of gestation. Amniocentesis revealed a karyotype of 47,XX,+21[3]/46,XX[17], and multiplex ligation-dependent probe amplification (MLPA) on uncultured amniocytes revealed rsa X(P095) × 2, (13, 18, 21) × 2. She underwent cordocentesis (cord blood sampling) at 21 weeks of gestation which revealed a karyotype of 47,XX,+21[2]/46,XX[48]. At 27 weeks of gestation, she was referred to our hospital for genetic counseling, and repeat amniocentesis revealed a karyotype of 46,XX in 20/20 colonies. Quantitative fluorescent polymerase chain reaction (QF-PCR) analysis on the DNA extracted from uncultured amniocytes and parental bloods excluded uniparental disomy (UPD) 21. Array comparative genomic hybridization (aCGH) analysis on the DNA extracted from uncultured amniocytes revealed arr (1-22,X) × 2, Y × 0 with no genomic imbalance. Interphase fluorescence in situ hybridization (FISH) analysis on 104 uncultured amniocytes detected one cell (1/104 = 0.9%) with trisomy 21, while the rest cells were disomy 21, compared with 0% (0/100) in the normal control. The woman was encouraged to continue the pregnancy. The pregnancy was carried to 38 weeks of gestation, and a 2771-g female baby was delivered no phenotypic abnormality. aCGH analysis on the cord blood showed arr (1-22,X) × 2, Y × 0 with no genomic imbalance. The umbilical cord had a karyotype of 47,XX,+21[3]/46,XX[37]. The placenta had a karyotype of 46,XX. When follow-up at age 3½ months, the neonate was phenotypically normal and had normal development. The peripheral blood had a karyotype of 46,XX in 40/40 cells. Interphase FISH analysis on buccal mucosal cells detected normal disomy 21 cells in 100/100 cells. Conclusion: Low-level mosaic trisomy 21 at amniocentesis and cordocentesis in the second trimester can be associated with perinatal progressive decrease of the trisomy 21 cell line and a favorable fetal outcome.